Gonadotropowa i immunotropowa aktywność nanodiamentów oraz ich koniugatów z Neb-kolostatyną i jej analogami u chrząszcza Tenebrio molitor - Nowicki, Patryk (My University, 2020)
W pracy po raz pierwszy wprowadzono za pomocą nanodiamentów (NDs)owadzi peptyd przez kutikulę do organizmu owada. Wykazano, że osiem bardziej hemocytotoksycznych analogów Neb-kolostatyny wykazuje silną aktywność immunoinhibicyjną i gonadoinhibicyjną oraz zaburza rozwój embrionalny i metamorfozę T. molitor. Udowodniono, że NDs nie mają aktywności immunotropowej ani nie wpływają na metamorfozę owada, lecz opóźniają składanie jaj i wylęgalność larw ze złożonych jaj. Zidentyfikowano cztery najbardziej aktywne analogi, które w kompleksach z NDs przenikały kutikulę owada obniżając jego odporność, rozród i rozwój.

In this work, for the first time, an insect peptide was introduced using of nanodiamonds (NDs) through the cuticle into the body of an insect. Eight more haemocytotoxic Neb-colloostatin analogues have been shown to exhibit strong immunoinhibitory and gonadoinhibitory activity, and to interfere with embryonic development and metamorphosis of Tenebrio molitor. It has been demonstrated that NDs do not have immunotropic activity and do not affect insect metamorphosis, but delayed egg laying and larvae hatching from laid eggs. Four most effective analogues were identified which, in complexes with NDs, penetrated the insect cuticle reducing its immunity, reproduction and development.
The gonadotropic and immunotropic activity of nanodiamonds and their conjugates with Neb-colloostatin and its analogs in the Tenebrio molitor beetle
Wydział Biologii
Keywords: Neb-kolostatyna; analogi Neb-kolostatyny; nanodiamenty; owad; bioinsektycydy; Neb-colloostatin; Neb-colloostatin analogs; nanodiamonds; insect; bioinsecticides